(untitled) (American Journal of Business Management, Economics and Banking, 2026)
This study examines the integration of Uzbekistan into the system of international economic relations, the development of foreign trade, and the regulatory framework supporting international cooperation. It analyzes reforms implemented within the Action Strategy, investment policy, and the dynamics of capital investments. Particular attention is given to centralized investments, budget funds, the Reconstruction and Development Fund, and state-guaranteed loans.